Patterns of maternal and child health services utilization and associated socioeconomic disparities in sub-Saharan Africa - Claire Najjuuko; Ziqi Xu; Samuel Kizito; Chenyang Lu; Fred M. Ssewamala (Nature Communications)
Abstract Under-five mortality remains a global health issue, especially in sub-Saharan Africa, where preventable conditions largely drive the high mortality rates. Understanding the heterogeneity in utilization of reproductive, maternal, newborn, and child health services is crucial for reducing under-five mortality. Here we show that among 9307 under-five mortality cases across 31 sub-Saharan African countries (2014–2024), maternal and child health service utilization falls into three distinct patterns—lowest, medium, and highest. Socioeconomic status strongly predicts subgroup membership: higher maternal education, employment, urban residence, and wealth are associated with lower odds of being in the lowest utilization group. Inequality indices further reveal disparities by education, wealth, residence, and employment. Our findings show a strong link between socioeconomic status and maternal and child health services utilization. To address under-five mortality in sub-Saharan Africa, targeted strategies are needed to improve access and uptake of essential health services among socioeconomically disadvantaged groups.